FUNGSI, HAK DAN KEWAJIBAN BADAN PERMUSYAWARATAN DESA DAN ANGGOTA BADAN PERMUSYAWARATAN DESABERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Ramli Ramli (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2021)
The Village Consultative Body or what is referred to by another name is an institution that carries out government functions whose members are representatives of the village population based on regional representation and are determined democratically. In this Law there is also a function of the Village Consultative Body, which is contained in Article 55, namely First: Discussing and agreeing on the Draft Village Regulation with the Village Head. Second: To accommodate and channel the aspirations of the Village community; and Third: Supervise the performance of the Village Head. The Village Consultative Body is highly expected by the Village community, because with this institution all the aspirations and wishes of the community will be channeled, therefore, every individual elected to be a member of the Village Consultative Body must be able to represent the community in the respective regions that elect him. In carrying out its role, the Village Consultative Body so that what is the hope and desire in advancing the Village can be achieved as well as possible. Given that the village head cannot do it by himself and must get support and assistance from the existence of the Village Consultative Body